Corneal temperature in patients with dry eye evaluated by infrared radiation thermometry. Issue 1 (January 1996) - Fujishima, H; Toda, I; Yamada, M; Sato, N; Tsubota, K
Abstract : AIMS: The corneal temperature change following each blink was investigated in patients with dry eye using an infrared radiation thermometer. METHODS: Twenty patients with dry eye and 20 normal controls were enrolled in this study. Subjects kept their eyes open for 10 seconds without blinking and corneal temperature was measured every second with a recently improved infrared radiation thermometer. RESULTS: In the 20 patients with dry eye, corneal temperature change after keeping the eye open for 10 seconds was 0.21 (SD 0.06) degree C while it was 0.61 (0.28) degree C in the 20 normal patients (p = 0.0001). In an exponential equation, the inclination of the slope of a patient with dry eye was smaller than the normal. The correlation coefficient was r = 0.79 (0.16) in patients with dry eye and r = 0.90 (0.07) in normal patients. The mean K value of patients with dry eye was 0.20 (0.13)/second and that of normal subjects was 0.31 (0.19)/second (p = 0.03). CONCLUSION: Findings demonstrate the usefulness of this thermometer for measuring corneal temperature in the evaluation of dry eye. Decrease in corneal temperature with each blink in patients with dry eye was smaller than in normal subjects.